COMMUNITY EMPOWERMENT ON SUSTAINABLE RABBIT FARMING BASED ON ZERO WASTE TO INCREASE INCOME IN DESA ALUE BULOH , KECAMATAN BIREM BAYEUN KABUPATEN ACEH TIMUR - Rozalina; Kiagus Muhammad Zain Basriwijaya; Thursina Mahyudin; Zulhilmi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The aim of this activity is to increase partners' income and skills. The activity began with an opening ceremony, delivery of materials, technical training on housing for rabbit cultivation, training on rabbit cultivation seeds, assistance in technical rabbit marketing strategies, monitoring and evaluation of activities, and details of solutions offered by the PKM proposing team systematically with priority partner problems. The program package provided is in the form of 50 baby rabbits or 10 boxes of 5 rabbits in a cage measuring 7 x 17 m or 120 m2 , with a cage density of 5 animals/m2 , feed equipment and beverage equipment as well as automatic heating as well as vaccines and medicines. The results of a survey conducted by the service team show that the problems faced by farmer partners are: 1.) Lack of partner understanding about rabbit farming which can increase partner income and skills. 2.) Expenditures on animal feed which are quite expensive so that alternative animal feed is needed are vegetables around people's homes.